Registration of TCLF-AN-105 Triticale - Lozano del Rio, JA; Lozano Cavazos, C.J.; Ibarra Jimenez, L; Cruz Lázaro, E. de la; Colin Rico, M; Zamora Villa, M; Mergroum, M; Pfeiffer, Wolfgang H.; Ammar, K (Wiley, 2010)
TCLF-AN-105 (Reg. No.TCL-009 251104, México; Reg. no. CV-31, PI 658496) intermediate triticale (× Triticosecale Wittmack) was developed by the International Maize and Wheat Improvement Center (CIMMYT), México, and reselected and released as a forage cultivar in Mexico by the Universidad Autónoma Agraria Antonio Narro (UAAAN). TCLF-AN-105 was selected from the progeny of the cross CT776.81//TESM01/MUSK603 produced in the Yaqui Valley, México, in 1989. CT776.81 and TESM01/MUSK603 are two parental lines (winter and spring triticale, respectively) developed by CIMMYT. TCLF-AN-105 was released because of its biomass production, cycle duration and nutritive value. The selection was based primarily on forage and agronomic characteristics and resistance to stem and leaf rust. TCLF-AN-31 winter triticale (Reg. no. CV-25, PI 620762), released as a forage cultivar by the UAAAN in 1992 (México Reg. No. TCL-07 080592) was used as reference cultivar.